2004
DOI: 10.1039/b409221j
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of cervimycin C, an aromatic polyketide antibiotic bearing an unusual dimethylmalonyl moiety

Abstract: Cervimycin C is the major component of an antibiotic complex produced by Streptomyces tendae HKI-179 consisting of a tetracycline-type aglycon, six tridesoxysugars and a rare dimethylmalonyl moiety. The biosynthetic origin of cervimycin was studied by molecular studies and feeding experiments, which reveal that the dimethylmalonate unit is not derived from malonate, but from valine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Labeling studies in our laboratory revealed that this novel dimethylmalonyl unit is derived from valine, and not from a malonate precursor, as one might assume. [37] The results of antimicrobial testing showed that all cervimycins A-D proved to be highly active against various Gram-positive bacteria, such as Bacillus subtilis ATCC 6633, Staphylococcus aureus SG511, and multi-drug-resistant S. aureus 134/93 (MRSA), and displayed potencies comparable to those of tetracycline, vancomycin, and ciprofloxacin (Table 1). More importantly, they are also highly active against efflux-resistant S. aureus EfS4 and vancomycin-resistant Enterococcus faecalis 1528 (VRE) within a MIC range of 1.6-12.5 mg mL À1 , in contrast to tetracycline, vancomycin, or ciprofloxacin, which are ineffective against VRE and EfS4, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…Labeling studies in our laboratory revealed that this novel dimethylmalonyl unit is derived from valine, and not from a malonate precursor, as one might assume. [37] The results of antimicrobial testing showed that all cervimycins A-D proved to be highly active against various Gram-positive bacteria, such as Bacillus subtilis ATCC 6633, Staphylococcus aureus SG511, and multi-drug-resistant S. aureus 134/93 (MRSA), and displayed potencies comparable to those of tetracycline, vancomycin, and ciprofloxacin (Table 1). More importantly, they are also highly active against efflux-resistant S. aureus EfS4 and vancomycin-resistant Enterococcus faecalis 1528 (VRE) within a MIC range of 1.6-12.5 mg mL À1 , in contrast to tetracycline, vancomycin, or ciprofloxacin, which are ineffective against VRE and EfS4, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…In the course of a screening program for novel antibiotics from strains obtained from Grotta dei Cervi, a cave in Italy, Herold et al ( 2004 ) identified a bioactive complex, Cervimycins A–D, from a strain of Streptomyces tendae . Cervimycins are potent antibiotics against multidrug resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus faecalis (VRE) strains (Herold et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…UPLC analysis and dereplication of the compounds present in five peaks against our in-house database ( Pérez-Victoria et al, 2016 ), and the Chapman & Hall Dictionary of Natural Products Compounds ( Buckingham, 2013 ) revealed that, based on the absorption spectrum and mass analysis, they contain compounds compatible with members of the cervimycins family ( Figure 3B ), a tetracycline-type compound with six 6DOHs attached. They were identified as antibiotic HKI 10311129 ( 15, m/z = 1113.4765 [M+H] + ), antibiotic A2121-1 ( 16, m/z = 1199.4794 [M+H] + ), cervimycin D ( 17, m/z = 1213.4939 [M+H] + ), cervimycin C ( 18 , m/z = 1227.5115 [M+H] + ) and cervimycin A ( 19 , m/z = 1226.5152 [M+H] + ) ( Herold et al, 2004 , 2005 ).…”
Section: Resultsmentioning
confidence: 99%